2019
DOI: 10.3390/polym11050823
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Nickel Coating of Carbon Fiber for Thermally and Electrically Conductive Fiber Reinforced Composites

Abstract: In this paper, the thermal and electrical conductivity and mechanical properties of fiber reinforced composites produced from nickel- and copper-coated carbon fibers compared to uncoated fibers are presented. The carbon fibers were processed by our prepreg line and cured to laminates. In the fiber direction, the thermal conductivity doubled from ~3 W/mK for the uncoated fiber, to ~6 W/mK for the nickel, and increased six times to ~20 W/mK for the copper-coated fiber for a fiber volume content of ~50 vol %. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Thermal stability of Cu coating CF was enhanced because of the thermal stability of Cu and the strong interaction bonds after chemical treatment. This agrees with the results of Bard et al [11] and Mohd et al [13].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Thermal stability of Cu coating CF was enhanced because of the thermal stability of Cu and the strong interaction bonds after chemical treatment. This agrees with the results of Bard et al [11] and Mohd et al [13].…”
Section: Resultssupporting
confidence: 94%
“…In addition to the carbon peak originating from the carbon substrate only copper features were noticed, presumably formed as an artifact due to manipulating with the copper-coated CF [10]. Table 2 shows the TGA results for Ep/CF, Ep/chemical treated CF and Ep/Cu coated CF composites at different treatment temperatures have a 5% weight loss (T 5 ) below 450 °C , due to the physically decomposition and adsorption of water [11,12]. It can be noted that, for Ep/Cu coated CF, the temperature for the 5% weight loss increased to 322 °C when compare with that of the Ep/CF and Ep/chemical treated CF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the thermal conductivity varies linearly with the nanoparticles concentration. Bard et al 23 have studied the influence of a metal coating on the thermal conductivity of laminates. They have shown that the metal coating was very effective to enhance the thermal conductivity, both in the transverse and in fiber direction.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent advances, metallic and carbon materials, such as graphene and carbon nanotubes, have been used to enhance thermal conductivity due to their free electrons, which are much more efficient in heat transfer. Unfortunately, adding metallic or carbon particles into polymers will also cause a substantial increase in the electrical conductivity of the composites [13,14,15]. Moreover, ceramic fillers, such as Al 2 O 3 , AlN, BN, SiC and Si 3 N 4 , with different shapes and sizes, have been studied for thermally conductive and electrically insulating composites, as they lack free electrons, so the heat transfer is predominantly realized through phonons [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%